Statistical Software Usability for Novice Research Students in the Social Sciences: An Eye-Tracking Study - Sedigheh Abbasnasab Sardareh; Gavin T. L. Brown; Paul Denny (Journal of Statistics and Data Science Education, 2025)
Many social science research students struggle to master statistical data analysis and exhibit low ability in using statistical software tools. The current study tackles the possibility that the design of statistical software systems explains the difficulty that students encounter when conducting statistical data analysis. An eye-tracking experiment randomly assigned 24 students to either SPSS or jamovi software to complete a linear regression task so as to evaluate the usability of the two systems. Upon task completion, each participant “thought aloud” as they watched a video of their own eye-tracked performance. Performance quality was better in jamovi compared to SPSS in terms of speed, fixation counts, and gaze duration. Heat maps of gaze time and location showed that in jamovi, the more restricted range of functions supported success compared to the many options provided in SPSS menus. Thematically analyzed think-alouds confirmed that design features such as simple menus and automatic display of results contributed to successful problem-solving by these novices.